2017
DOI: 10.2196/preprints.9691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlations between objective behavioral features collected from mobile and wearable devices, and depressive mood symptoms in affective disorders: A systematic review (Preprint)

Abstract: Background: A number of studies have recently reported on the correlation between objective behavioral features collected via mobile and wearable technologies and mood symptoms in affective disorders (unipolar disorder and bipolar disorder). However, individual studies have reported on different and sometimes contradicting results and no quantitative systematic review of the correlation between objective behavioral features and mood symptoms has been published. Objective: The objectives of this systematic revi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…This moment-by-moment quantification of the individual-level human phenotype in situ using data from personal digital devices is referred to as "digital phenotyping" (13,14). There is now a growing body of research demonstrating that digital phenotyping data may enable the identification of people suffering from or at risk of developing mental disorders, in some cases even before symptoms are visible (or detectable) using traditional methods (11,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This moment-by-moment quantification of the individual-level human phenotype in situ using data from personal digital devices is referred to as "digital phenotyping" (13,14). There is now a growing body of research demonstrating that digital phenotyping data may enable the identification of people suffering from or at risk of developing mental disorders, in some cases even before symptoms are visible (or detectable) using traditional methods (11,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Beiwinkel et al (20) found that the total distance traveled had a significant negative relationship with clinical manic symptoms in patients diagnosed with bipolar disorder (beta = −0.37). Finally, in a meta-analytic review of studies assessing the correlation between smartphone and wearable device data and affective disorders, Rohani et al (15) revealed that the association between time spent at home and depressive symptoms was the most consistently significant finding of any smartphone-derived feature in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Edwards et al [23], they found a significant increase in depression scores (F = 11.85, p = .001) in the group of healthy young adults that were asked to minimize physical steps for one week. In an extensive systematic review, Rohani et al [21] revealed a consistent negative correlation among studies between vigorous activity and depressive symptoms.…”
Section: Activity Category On 'Good-days'mentioning
confidence: 96%
“…To keep a circadian rhythm, denoted here as 'diurnal rhythm', have shown a positive statistically significant correlation with mood [21]. This relation is explored by defining 'diurnal rhythm' as the most common AC within each hour.…”
Section: Circadian Rhythmmentioning
confidence: 99%